Determination of Total Flavonoid Levels Of Cinnamon Leaf Infusion (Cinnamomum burmanni (Nees & T.Nees) Blume.) Using UV-Vis Spectrofotometry - Tri Nova Lovena; Dewi Gulyla Hari; Encik Juliansyah Arief (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Cinnamon leaves (Cinnamomum burmanni (Nees & T.Nees) Blume.) are natural plants used as traditional medicine because they have secondary metabolite compounds, namely flavonoids, tannins, saponins, alkaloids, and triterpenoids. Objective: This study aims to determine the total flavonoid compound levels found in cinnamon leaves (Cinnamomum burmanni (Nees & T.Nees) Blume.). Methods:The extraction method used is the infusa method using aquadest solvent. Qualitative analysis used phytochemical screening and quantitative analysis used is by UV Vis Spectrophotometry with standard comparison using quercetin. Results: For parametric data analysis using One Way Annova analysis. The results of phytochemical screening examination of cinnamon leaves (Cinnamomum burmanni (Nees & T.Nees) Blume.) are positive for flavonoid compounds with the total flavonoid compound content using the UV-Vis Spectrophotometry method is 0.5691 mgQE/g, and the results of parametric data analysis using One Way Annova analysis show a significant value of flavonoid content of 1.000> 0.05. This indicates that the flavonoid levels in the sample are relatively stable and homogeneous, so the treatments applied did not result in significant variation. This may suggest that the treatment factors in the study did not significantly affect the amount of flavonoids contained in the cinnamon leaf extract. Thus, the detected flavonoid content is likely more influenced by the natural characteristics of the plant rather than by the treatments tested. Conclusion: The cinnamon leaf (Cinnamomum burmanii) showed a positive result for the presence of flavonoid compounds.